MEAT EFFICIENCY OF HEREFORDS OF SIBERIAN REPRODUCTION - Inerbaev B.O.; Inerbaeva A.T. (Техника и технология пищевых производств)
The problem of meat quality becomes an actual one due to the increase of demand for beef. In restaurants and supermarkets, the price of the most deficient meat - marbled meat - is 800-1300 rub/kg and it is imported mainly from abroad (Australia, the USA). In Russia, such meat is not produced and home plant-breeding-tribal work has not accented on obtaining meat of particular quality. This factor being genetically determined and inherited, we put forward the task to study the meat productivity of Herefords of Siberian reproduction and the quality of meat with a method based on the use of imported bio-products. The live weight and average daily weight gain of bull-calves have been determined. Control slaughter of bull-calves of Herefords breed has been done. Trade and commercial cuts of half carcasses have been determined. The biochemical structure of muscles of meat has been investigated. By results of researches it is revealed that the use of a seed of a servicing bull of the Australian selection of Allendale Superstar B21 made it possible to increase selection differential on live weight to 32 kg (7.3%), and on a daily live weight gain to 178.7 g (17.3%). The superiority of bull-calves of the experimental group over the control one in terms pre-slaughter live weight was 24.0 kg (5.5%). The slaughter yield was 1.7% higher and was 59.4%. According to the Australian scale the marbling of the longest muscle of a back of experimental bull-calves was 6 points, and that of a control one - 2-3 points. The use of the Herefords servicing bull seed can accelerate the selection process in meat cattle breeding of the region.